SCREENING AND IDENTIFICATION OF A NOVEL ALKALINE LIPASE PRODUCING BACTERIUM - FRANCOIS N. NIYONZIMA; SUNIL S. MORE (International Journal of Pharma and Bio Sciences, 2013)
The lipase producing bacteria were screened from the soil both qualitatively by Tween 80, rhodamine B agar assays and quantitatively by titrimetry with the objective of finding a bacterial strain capable of producing an alkaline lipase. The higher lipolytic activity of 17.43 U/ml was recorded for the isolate L13. Traditional methods viz. morphological, cultural and biochemical characteristics were carried out to identify the most potent bacterial producer of an alkaline lipase. The isolate L13 was identified as Bacillus flexus. Based on nucleotides homology and phylogenetic analysis, the isolate displayed 99% sequence similarity to Bacillus flexus and was named Bacillus flexus strain XJU-1(GenBank Accession Number: DQ837542.1). The screened Bacillus flexus from the present study can be exploited for the industrial production of an alkaline lipase that can be used in detergent and leather industries since the isolate is producing higher amounts of enzyme under alkaline conditions.